Hayai-Annotation: A functional gene prediction tool that integrates orthologs and gene ontology for network analysis in plant species - Andrea Ghelfi; Sachiko Isobe (Computational and Structural Biotechnology Journal)
Hayai-Annotation, an annotation tool powered by the R-shinydashboard browser interface, implements a workflow that integrates sequence alignment using DIAMOND against UniProtKB Plants and ortholog inference using OrthoLoger. We here propose a pipeline to explore genome evolution and adaptation from a different perspective, by creating a network considering orthologs and gene ontology as nodes, with edges based on the annotation for each gene. This approach aims to improve the visualization of conserved biological processes and functions, highlight species-specific adaptations, and enhance the ability to infer the functions of uncharacterized genes by comparing edge patterns across species. To our knowledge, this is the first attempt to build a network using annotated OrthoDB orthologs and Gene Ontology terms (Molecular Function and Biological Process) as nodes, providing a comprehensive view of gene distribution and function in plant species. The GO annotation accuracy was assessed by the CAFA-evaluator, demonstrating that the accuracy of this version of Hayai-Annotation exceeded that of the benchmark, InterProScan. The updated Hayai-Annotation enhances ortholog analysis functionality, allowing for evolutionary insights from gene sequences, and is expected to contribute significantly to the future development of plant genome analysis.